THE BEBBINGTON QUADRILATERAL TRAVELS INTO THE EMPIRE. - Elliott, Kelly Cross (Fides et historia, 2015)
This essay examines the character of British evangelical religion that is based on the Bebbington quadrilateral, which was brought out of Great Britain by evangelical missionaries beginning in the late 18th century. It provides a background of the Baptist Missionary Society's work in Serampore in Bengal, India in 1795 whose particular problems shaped the character of missionary evangelicalism. Also discussed is the state of Indian activism at Serampore from 1880 to the 1820s.